Determinants of Strand Selection among Senior High School Students - Dulalas, Sherry Lyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the factors influencing Senior High School (SHS) strand selection among students in the District of Dauis and aimed to inform the development of a career guidance program that supports informed decision-making and alignment with long-term career goals. Grounded in Gottfredson’s theory of circumscription and compromise, Holland’s theory of personality–environment fit, and Bronfenbrenner’s Ecological Systems Theory, the study conceptualized strand selection as a product of both internal motivations and external environmental influences. An explanatory sequential mixed-method design was employed, involving 150 Grade 11 and 12 students selected through stratified random sampling, followed by qualitative interviews with purposively selected college students. Data were collected using a modified questionnaire and semi-structured interview guide, and analyzed through descriptive and inferential statistics alongside thematic analysis. Findings revealed that personal interest was the most significant determinant of strand selection, while family and school-related factors were moderately influential, and peer influence had minimal impact. No significant relationship was found between demographic variables and personal or school-related influences, although family and social influences showed selective associations with gender, grade level, and strand. Qualitative results highlighted challenges such as strand-course misalignment, financial constraints, parental guidance, limited strand availability, and adjustment difficulties in higher education. The study concludes that strand selection is primarily driven by intrinsic motivation, supported by external contextual factors. It recommends the implementation of comprehensive career guidance programs emphasizing self-awareness, family involvement, and institutional support. This study aligns with Sustainable Development Goal (SDG) 4 on Quality Education and SDG 8 on Decent Work and Economic Growth by promoting informed educational choices and improved alignment between education and employment pathways. Its sustainability impact lies in strengthening educational and institutional systems, reducing skills mismatch, and enhancing workforce readiness and socio-economic development.
Keywords: Career Guidance; Family Influence; Personal Interest; School-Related Factors; Senior High School Strand Selection; Social Influence